2021
DOI: 10.1007/s00262-021-02931-6
|View full text |Cite
|
Sign up to set email alerts
|

CMTM6 expression in M2 macrophages is a potential predictor of PD-1/PD-L1 inhibitor response in colorectal cancer

Abstract: Background CMTM6 is a novel key regulator of PD-L1. High expression of both CMTM6 and PD-L1 may predict the benefit of PD-1 axis blockade in lung cancer. We aimed to investigate the expression pattern of CMTM6 between mismatch repair-defective (dMMR) and mismatch repair-proficient (pMMR) colorectal cancer (CRC) tissues and assess its correlation with the response to PD-1/PD-L1 pathway blockade. Methods Immunohistochemistry (IHC) was used to analyze CMTM6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
(53 reference statements)
1
20
0
Order By: Relevance
“…A recent study indicates that CMTM6 is expressed on CD8 + T cells and CD163 + M2 macrophages in colorectal cancer tissues. Its expression in T cells and M2 macrophage is associated with clinical benefit and response to immunotherapy [27]. Another study found the expression of CMTM6 mainly on CD68 positive macrophages in the non-small-cell lung cancer (NSCLC), and its expression is correlated with longer overall survival in the patients with immunotherapy [28].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicates that CMTM6 is expressed on CD8 + T cells and CD163 + M2 macrophages in colorectal cancer tissues. Its expression in T cells and M2 macrophage is associated with clinical benefit and response to immunotherapy [27]. Another study found the expression of CMTM6 mainly on CD68 positive macrophages in the non-small-cell lung cancer (NSCLC), and its expression is correlated with longer overall survival in the patients with immunotherapy [28].…”
Section: Discussionmentioning
confidence: 99%
“… B7 family, Vimentin, PD-L1 [ 77–81 ] GC Higher a useful prognostic indicator [ 39 , 40 ] CRC Higher Associated with an active immune microenvironment, a favorable prognosis. [ 84 , 85 ] NSCLC Lower in lung adenocarcinoma Correlated with PD-L1 expression and immune cells infiltration [ 4 , 86–89 ] HNSCC Higher Promotes cell proliferation and invasion; drives cisplatin resistance; Induced M2-like macrophages polarization Wnt/β-catenin, TGFβ; ENO-1/AKT/GSK3β; ERK1/2 [ 90–94 ] Gliomas Higher Regulating T cell activation and antitumor and responses [ 7 ] Undifferentiated pleomorphic sarcoma Correlated with the strong expression of PD-L1 [ 95 ] Glioblastoma Higher (mRNA)* - [ 36 ] CMTM7 HCC Lower Inhibits cell growth and migration …”
Section: Characteristics Of Cmtm Familymentioning
confidence: 99%
“…75 Meanwhile, the expression status of CMTM6 in M2 macrophages may more accurately predict the drug response to PD-1/PD-L1 inhibitors in CRC patients. 85 To date, the roles of other CMTM members in CRC, except for CMTM3, 4, and 6, are largely unknown.…”
Section: Cmtm Family Members In Digestive System Cancersmentioning
confidence: 99%
“…(18,19,(21)(22)(23)(24). Remarkably, CMTM6/PD-L1 coexpression suggested a poorer prognosis (20,(25)(26)(27), but instead a better prognosis when ICB therapies intervened (28)(29)(30). However, some contradictory findings have also been reported, indicating a complex role for CMTM6 in clinical cancers such as non-small cell lung cancer (NSCLC) (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%